Monitoring Local Regional Hemodynamic Signal Changes during Motor Execution and Motor Imagery Using Near-Infrared Spectroscopy - Iso, Naoki; Moriuchi, Takefumi; Sagari, Akira; Kitajima, Eiji; Iso, Fumiko; Tanaka, Koji; Kikuchi, Yasuki; Tabira, Takayuki; Higashi, Toshio (Frontiers in Physiology, 2016)
The aim of this study was to clarify the topographical localization of motor-related regional hemodynamic signal changes during motor execution (ME) and motor imagery (MI) by using near-infrared spectroscopy (NIRS), as this technique is more clinically expedient than established methods (e.g. fMRI). Twenty right-handed healthy subjects participated in this study. The experimental protocol was a blocked design consisting of 3 cycles of 20 s of task performance and 30 s of rest. The tapping sequence task was performed with their fingers under 4 conditions: ME and MI with the right or left hand. Hemodynamic brain activity was measured with NIRS to monitor changes in oxygenated hemoglobin (oxy-Hb) concentration. Oxy-Hb in the somatosensory motor cortex (SMC) increased significantly only during contralateral ME and showed a significant interaction between task and hand. There was a main effect of hand in the left SMC. Although there were no significant main effects or interactions in the supplemental motor area (SMA) and premotor area (PMA), oxy-Hb increased substantially under all conditions. These results clarified the topographical localization by motor-related regional hemodynamic signal changes during ME and MI by using NIRS.